An incident of lichen planus correlated to a certain brand of amlodipine: a case report - Alsenani, May A.; Albulayhid, Hissah A.; Alrayes, Nouf A.; Abudeeb, Razan A.; Alkhudairy, Reyof K.; Aljamaan, Salwa N.; Alkhamees, Sadeem A.; Alotai, Lena A. (International Journal Of Community Medicine And Public Health, 2024)
As the etiology of oral lichen planus (OLP) remains unclear most literature suggests that genetic, hepatitis c, systemic diseases, hypersensitivity to dental material and drug reactions can be contributing factors of OLP. However, as malignant transformation is a possible sequence of OLP, more efforts towards studying the etiology and OLP-inducing health conditions, materials, and drugs should be taken. We report a case of OLP induced by commonly prescribed antihypertensive, amlodipine specifically the commercial drug Amlocard to further discuss its association with OLP and how the active ingredient (amlodipine) might not be the actual cause of such reaction. In our case, a 60-year-old Saudi non-smoker housewife presented at the Dental University Hospital of King Saud University in Riyadh with multiple oral lesions on her tongue and bilaterally on the buccal mucosa for two-month duration. She also complained of pain and burning sensation over the areas of oral lesions while eating, especially when eating hot or spicy food. Otherwise, there were no associated numbness or loss of taste. The patient reported the following non-oral symptoms: itching of pubic area, skin-lesion on her back and chest, vaginal and anal lesions. Manifestation of OLP started 3.5 months after replacing her antihypertensive medication 5 mg Amlor (amlodipine) once per day to 5 mg Amlocard (amlodipine) twice per day. Diagnosis was confirmed after histopathological report of the incisional biopsy of the oral lesions to be indeed OLP. Satisfactory results were obtained after changing the medication back to Amlor with the same original dose and prescribing prednisolone oral solution 15 ml/5 mg for two weeks, Clobetasol propionate ointment 25 mg and nystatin suspension 100000 units to elevate oral symptoms. Amlodipine-associated lichen planus is an inflammatory reaction with different systematical manifestation, early recognition of signs and symptoms and frequent follow up is standard of treatment to recognize any unwanted malignant progression of the lesion.